Design, Development, and Delivery of Salbutamol Sulfate from an Adhesive Matrix System. Issue 2 (1st February 2016) - Bhattacharya, Shiv Sankar; Banerjee, Subham
Abstract : The objective of the present investigation was to design, develop, and evaluate the skin delivery of salbutamol sulfate from a drug-in-adhesive matrix type transdermal patch formulation. Initial formulation design and development experiments were conducted to optimize the formulation parameters before skin delivery in rats. The effects of two different types of pressure sensitive adhesives and permeation enhancers on skin transport of salbutamol sulfate across excised rat skin were investigated methodically. For ex-vivo skin permeation studies, the percutaneous absorption of salbutamol sulfate from a drug-in-adhesive matrix patch across excised rat skin were evaluated using a modified Franz-diffusion cell apparatus at a skin temperature (32°C). Further the fabricated adhesive matrix patches were also characterized by scanning electron microscopy, Fourier transform infrared spectroscopy, X-ray diffraction study, and differential scanning calorimetry analyses. Drug containing adhesive matrix patches showed sustained release property without showing any incompatibility in adhesive matrix system. This suggests that the transdermal application of salbutamol sulfate in a drug-in-adhesive matrix type transdermal patch may be used for the treatment for asthma patients.